Enhanced photoelectrochemical water-splitting performance of SrNbO2N photoanodes using flux-assisted synthesis method and surface defect management. Issue 4 (28th January 2020) - Yang, Yingchen; Lou, Zirui; Lei, Weisheng; Wang, Yichen; Liang, Rong; Qin, Chao; Zhu, Liping
Abstract : Particle-assembled SrNbO2 N photoanodes were obtained using flux-assisted nitridation reaction. The optimal experimental parameters were studied for SrNbO2 N particles with minimum surface defects and high crystallinity. Abstract : Perovskite SrNbO2 N particles were directly synthesized using a one-step thermal nitridation method with chloride flux and subsequently annealed under an inert Ar flow. By suitable adjustment of the flux synthesis parameters, including the nitridation temperature and the composition of the molten salt, preferable experimental conditions were found to suppress the formation of surface Nb defects and obtain samples with high crystallinity. The different SrNbO2 N photoanodes were fabricated using the electrophoretic deposition (EPD) method followed by necking treatment. The SrNbO2 N photoanode prepared using the optimum experimental conditions (nitridation temperature: 850 °C, a molar ratio of flux SrCl2  : KCl = 2 : 1) exhibited the highest photocurrent density of 2.0 mA cm −2 at 1.23 VRHE under simulated sunlight (AM 1.5G 100 mW cm −2 ) in a 1 M NaOH electrolyte. In comparison, the other highly defective SrNbO2 N photoanodes demonstrated an unsatisfactory water oxidation performance, which demonstrates the necessity to reduce the destructive effect of defects in order to achieve a higher photocurrent density.